Energy Intake at Admission for Improving Activities of Daily Living and Nutritional Status among Convalescent Stroke Patients - NISHIYAMA, Ai (Neurol Med Chir (Tokyo), 2019)
Our aim was to clarify the nutritional status and energy intake needed for activities of daily living (ADL) improvement among convalescent stroke patients. This retrospective cohort study of stroke patients used data from the Japan Rehabilitation Nutrition Database. Mean energy intake per ideal body weight was 26 kcal/kg/day at 1 week after hospitalization. Patients were divided into two groups according to energy intake: ≥26 kcal/kg/day (high) and <26 kcal/kg/day (low). ADL was evaluated using Functional Independence Measure (FIM), and nutritional status was evaluated using the mini nutritional assessment short form score. We created an inverse probability weighted (IPW) model using propensity scoring to control and adjust for patient characteristics and confounders at the time of admission. The analysis included 290 patients aged 78.1 ± 7.8 years. There were 165 patients with high energy intake and 125 patients with low energy intake. FIM score was significantly higher in the high group compared with the low group (median 113 vs 71, P <0.001). FIM efficiency was also higher in the high group (median 0.31 vs 0.22, P <0.001). FIM efficiency was significantly higher in the high energy intake group than in the low energy intake group after adjustment by IPW (median 0.31 vs 0.25, P = 0.011). Nutritional status improvement was also higher in the high energy intake group after adjustment by IPW (60.6% vs 45.2%, P <0.001). High energy intake was associated with higher FIM efficiency and nutritional status improvement at discharge among convalescent stroke patients.